Liminalité et motivation paysagère - Richard Pereira de Moura (Projets de Paysage)
This paper aims to consider the fondamental role of liminality in the elaboration and motivation of a relational landscape architecture. Articulated around three mutually implicated components - the body, the world, the threshold – the article is an invitation to profoundly re-evaluate our understanding of humankind’s inscription on Earth as well as Earth’s inscription on humankind - on the way to their reconciliation. In light of this dynamic involvement, the discussion leads to a renewed idea of landscape ethics – in perpetual motion between the here and there, the mind and the flesh, the self and the other, the inside and the outside, the animate and the inanimate.